Planetary nebulae: a key tool to reconstruct the evolutionary history of stars - Ventura, Paolo; Tosi, Silvia; Dell’Agli, Flavia; Bianchi, Stefano (Frontiers in Astronomy and Space Sciences, 2025)
Planetary nebulae, among the most fascinating objects in the sky, have been extensively investigated in the past years, because their study provides important information on the low and intermediate mass stellar populations of the host environment, formed earlier than ∼100 Myr ago. We report on the recent progresses achieved in the study of this class of objects, regarding the dust and gas content of the nebula, which allows us to reconstruct the dust formation process occurred during the previous asymptotic giant branch phase, and the chain of events occurred since the stars leave the asymptotic giant branch until the planetary nebula stage. The possibility offered by these studies to assess the role played by the stars of low and intermediate mass as dust manufactures in the Universe is also commented.